II Encuentro Regional de Visibilidad - Cifuentes, Carlos; Chaviano, Orlando Gregorio; Correa, Pablo; Flórez, Fabio; Rincón Martínez, Omaira; Ovalle, Andrés (Universidad Autónoma de Bucaramanga UNAB, 2021)
01:04:23 horas